BUDAYA MEDIA DAN LAHIRNYA SPECTACLE SOCIETY (Televisi sebagai Voyeurism Zaman Modern) - Reza Aprianti (Wardah, 2014)
Starting from the habit of "peek" and want to know the problems that other people have indirectly fueled the spectacle culture and society becomes increasingly masiv with the help of mass media. This applies also in Indonesian society seen from the number of television programs on average gives a presentation that are peeking problems of others. Although this culture has become mass culture, based on research results are acceptable in some countries the effects of this culture more negatively charged than the positive.